Diffusion energy barrier of Au on Bi2Se3: theory and experiment. (24th September 2021) - Kidd, T E; Lukashev, P V; Stuelke, L; Gorgen, C; Roberts, S; Gu, G; Stollenwerk, A J
Abstract: The stability and diffusion of ultra-thin thermally deposited Au films on Bi2 Se3 was studied using scanning tunneling microscopy and density functional theory calculations. The Au/Bi2 Se3 interface is of interest as gold is predicted to provide excellent electrical contact while maintaining the spin-polarized characteristics of the electronic states in Bi2 Se3 that make the material attractive for spintronic applications. When deposited at room temperature, Au covers the surface with tightly packed islands of nanometer scale dimension. The surface morphology is stable up to 400 K. At this annealing temperature, Au atoms have sufficient energy to diffuse across the surface and aggregate into larger nanostructures. At 550 K, the Bi2 Se3 surface is only sparsely covered, and the Au has formed clusters with length scales 5–10 times larger than the original islands formed at room temperature. Comparison of the experiment and first principle calculation lead to the conclusion that the diffusion energy barrier for Au on Bi2 Se3 is as high as 0.47 eV, which is much larger than diffusion barriers on other van der Waals materials.